CHEMICAL MODIFICATIONS OF ALGINATE AND ITS DERIVATIVES - NATARAJ, DIVYA; REDDY, NARENDRA (International Journal of Chemistry Research, 2020)
Alginate is a polysaccharide obtained from seaweeds that are abundantly available and have shown great potential for diverse industrial applications. However, alginate lacks properties such as stability under aqueous conditions and it is difficult to control the rate of degradation of alginate-based materials, crucial for various medical applications. Therefore, researchers have modified alginate using physical or chemical approaches to enhance physical properties, biocompatibility, solubility and also to control the biodegradability of alginate-based materials. Crosslinking using ionic, covalent, photo and enzymatic approaches are one of the preferred methods for modifying the properties of alginates and its derivatives. Crosslinking binds the individual polymer chains with one another to form a network that enhances mechanical properties and stability. Among the different crosslinking approaches, ionic crosslinking provides biomaterials with limited stability whereas biomaterials with high mechanical stability can be prepared by covalent crosslinking. Although a wide variety of crosslinking chemicals and approaches are available to make alginate suitable for various applications, the methods used, properties and applications of the cross-linked materials vary significantly between studies. There are very few reports that have compared and evaluated the benefits of using different crosslinking approaches and the properties and applications of cross-linked alginate. In this review, the various methods of crosslinking alginates, their advantages, and limitations have been reviewed with particular emphasis on medical applications of alginate. The data for writing the review was obtained using search engines like Google scholar, Sci-hub and Sci finder and the keywords used include alginate, crosslinking, ionic, covalent, photo, enzymatic, biomedical applications.